The impact of ultraviolet wavelengths on broiler chicken performance, health and welfare - James, Charlotte (2021)
Qualities of the light environment affect the performance, health and welfare of broiler chickens. UVA light is visible to chickens and may facilitate improvements in welfare. UVB wavelengths promote endogenous vitamin D synthesis, which could support the rapid development of broilers. The aim of the study was to investigate the impacts of Ultraviolet wavelengths (UV) on performance health and welfare indicators. Day-old Ross 308 birds (n = 638) were randomly assigned to one of three lighting treatments: A) White Light Emitting Diode (LED) & supplementary UVA LED lighting (18-hour photoperiod); B) White LED with supplementary UVA & UVB fluorescent lighting providing 30 micro watts/cm2 UVB at bird level (for 8 hours of the total photoperiod to avoid over-exposure of UVB); C) White LED control group, representative of farm conditions (18-hour photoperiod). Birds were fed a commercial diet and kept at a final stocking density of 33kg/m2. Indictors measured were: (Performance) average daily gains, mortality, final weights, breast weights and leg weights. (health) bone mineral density, leg composition, bone measurements, tibia strength and severity of tibial dyschondroplasia. (welfare) feather condition, tonic immobility duration and walking ability, using the Bristol Gait Score. Growth was faster in male broiler chickens in treatment B, though slower in males in treatment A. Similar final weights were achieved in all treatments. Treatment A and B improved gait score, additionally heavier broilers in both treatments had improved walking ability compared to control broilers of similar weights. Treatment A also reduced fearfulness. There was no impact of either treatment on skeletal or ocular health measures. Together these results suggest UV wavelength supplementation may offer a promising husbandry refinement for commercial indoor lighting regimes; offering potential benefits to both bird welfare without compromising performance.